Professor Myron Kordubaṡ Contribution into Geographical Shevchenkiana - Rudenko, V; Grek, K (Journal of Education, Health and Sport, 2021)
The article deals with most essential specificities of creative approach and major results of regional geographical studies of Taras Shevchenko, an outstanding Ukrainian poet and painter, disclosed by Myron Korduba (1876 – 1947), Professor, Warsaw University, in his T. Shevchenko as Regional Ethnographer and Archaeologist. It was accentuated that, when studying nature and local people, Taras Shevchenko preferred “a good pencil-drawn sketch from nature”; focused on specific natural phenomena, characteristic for this or that locality; put people and community, their culture and everyday life into a center of his regional geographical cognition.
Keywords: Taras Shevchenko; Myron Korduba; regional geographical activity